Needs analysis for the visual auditory kinesthetic (VAK) model using smart floor in physical education, sports, and health learning in elementary schools - Widya Handayani; Hikmah Lestari; Siti Ayu Risma Putri; Muhsana El Cintami Lanos; Evi Megariani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study presents the needs of the VAK game model using Smart Floors in Physical Education, Sports, and Health learning for elementary school students. Using Smart Floors (a technology-based interactive surface) as part of technological advancements provides sports facilities that can enhance exercise, prevent injuries, and create a more engaging sports experience for elementary school students. A descriptive exploratory design with a mixed-method approach was used as the research method. The study was conducted at five elementary schools in Palembang. Participants involved as informants were 200 fourth and fifth-grade elementary students and five sports teachers. Data collection techniques were observation (direct surveys to schools), interviews, questionnaires, and documents. Data analysis techniques were carried out quantitatively and qualitatively. The results of the needs analysis concluded that teachers and students gave a positive response to the need for a Physical Education, Sports, and Health learning model, and with the percentage of 'agree' and 'strongly agree' responses from students reaching >70% for the audio and visual content aspects, strengthening the findings of this needs analysis. The most desired game model was based on traditional games, supported by technology. The VAK game model using Smart Floor was created to contain 1) content aspects (audio, visual, and kinesthetic), 2) process aspects (exploration, elaboration, and confirmation), and 3) impact aspects. Based on the findings of this needs analysis, the design of the VAK game model should be implemented using various traditional games. The research implications indicate that the findings provide a concrete basis for the design and development phase of the VAK game model, which is based on Smart Floors and traditional games.